Morphological performance and seasonal pattern of water relations and gas exchange in Pistacia lentiscus plants subjected to salinity and water deficit - Álvarez, Sara; Acosta-Motos, Jose Ramon; Sánchez-Blanco, María Jesús (Frontiers in Plant Science, 2023)
Soil water deficit and salinity represent a major factor impacting plant survival and agricultural production. The frequency and severity of both abiotic stresses are expected to increase in a context of climate change, especially in arid and semi-arid regions. This work studied the growth pattern, biomass and mineral distribution and the seasonal pattern of water status, photosynthetic rate and stomatal conductance in plant of Pistacia lentiscus grown under different levels of water deficit and salinity. P. lentiscus plants growing under greenhouse conditions were subjected to four irrigation treatments during 11 months: control (C, 1 dS m-1), moderate water deficit (MW, 1dS m-1, 60% of the control), severe water deficit (SW, 1 dS m-1, 40% of the control) and saline (S, 4dS m-1). The results show that Pistacia lentiscus plants were more affected by deficit irrigation than salinity. Deficit irrigation and salinity inhibited plant height, with reductions of 20%, 22% and 35% for S, MW and SW, respectively. Total leaf area was not modified by effect of the treatments, with the result that plant compactness increased in MW. The salt stressed plants only showed lower relative growth rate at the end of the experiment. Plants responded to saline or drought stress by increasing their osmotic adjustment, which was more pronounced under salinity. Saline plants had the highest values in Na+ and Cl- ions and the lowest values for K+/Na+ and Ca2+/Na+ ratios in leaves and stems, which is correlated with a decrease in growth, stomatal conductance, photosynthesis and stem water potential, and can be used as a diagnostic tool to assess plant tolerance to salinity stress. As a measure of plant hydration, relative water content was more sensitive to deficit irrigation than salinity, being a good indicator of water stress. P. lentiscus plants subjected to both deficit irrigation treatments exhibited an increase in their intrinsic water use efficiency, which is an important adaptation for plants growing in environments with water scarcity.